O uso de células tronco no tratamento do trauma raquimedular:uma revisão - Ramos, Camila da Silva Barbosa (2015)
The spinal cord injury is a condition where the individual loses partially or totally the motor capacity and it is still affected by systemic complications. Being the permanent treatment for the long-term paralysis undefined these patients has a cost to public health. With the technological and medical advances has been found a great potential in the use of stem cells for the treatment of this type of injury. The availability of multiple sources of adult mesenchymal cells suggests innovative and promising strategies but the research should be conducted with caution because of the little knowledge on some tumor modulations and the real effectiveness. As in any research for advances and setbacks, it is necessary expand the knowledge about whether these cells actually fulfill their therapeutic promise and which will be suitable for many different diseases. In this review, we will briefly discuss the mechanism and pathophysiology of spinal cord injury and potential sources of adult mesenchymal stem cells and their response to treatment with cell therapy in this specific group.